(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article discusses the psychological characteristics of preparing the younger generation for school in the context of additional education, as well as the pedagogical ideas of scientists on this topic, and the organization of education for preschool children.